2022
DOI: 10.3389/fsufs.2022.868479
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions in irrigated paddy rice as influenced by crop management practices and nitrogen fertilization rates in eastern Tanzania

Abstract: In rice production greenhouse gas emission (GHG) reduction is an important task for many countries, Tanzania included. Of global agricultural GHG emitted from rice fields, about 30 and 11% are represented by CH4 and N2O, respectively. For successful climate smart rice cultivation, rice management practices, including nitrogen fertilization are two key crucial components that need evaluation. The objective of this study was to evaluate the crop management practices and N fertilization on yield and greenhouse ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…The treatments within the rice-based cropping systems showed that straw incorporation triggered cumulative CH 4 emission faster than applying nitrogen application alone in the double rice, rice-wheat, and single rice cropping systems. This might be explained by the varied organic carbon substrate generated from microbial straw decomposition and environmental factors like precipitation and temperature in paddy fields [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The treatments within the rice-based cropping systems showed that straw incorporation triggered cumulative CH 4 emission faster than applying nitrogen application alone in the double rice, rice-wheat, and single rice cropping systems. This might be explained by the varied organic carbon substrate generated from microbial straw decomposition and environmental factors like precipitation and temperature in paddy fields [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…While tourism village that promotes paddy field covers as their main tourism features have the potential to emit GHG in the order of CO2 > CH4 > N2O. Moreover, fertilizer and irrigation to support the paddy field should be monitored and regulated through crop management practices and nitrogen regulations (Mboyerwa et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, environmentally friendly soil types, fertilizers, low-emission paddy varieties, sustainable cultivation technology, and selective water management [27] can reduce GHG emissions. Methane and carbon dioxide emissions from rice cultivation in paddy fields can be decreased using the paddy intensification system (SRI) [28].…”
Section: The Effect Of Paddy Production (Pcp) On Ghg Emissions In The...mentioning
confidence: 99%